Hierarchical porous catalyst for carbonyl sulfide hydrolysis as well as preparation method and application of hierarchical porous catalyst

The preparation of multi-stage porous alumina-based catalysts by soft template method solves the problem of short activity and life of existing catalysts in blast furnace gas, and achieves the effect of efficient removal of carbonyl sulfur from coal gas, with oxygen and sulfur resistance and good process performance.

CN119793430APending Publication Date: 2025-04-11INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510014514.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When used in blast furnace gas, existing catalysts have short activity and life due to the influence of oxidation and sulfides, making it difficult to achieve oxygen and sulfur resistance.

Method used

A multi-stage pore alumina-based catalyst was prepared by soft template method. By adjusting the ratio of template agent, pore reamer and acid solution, a catalyst structure with large pores and mesoporous is formed, which improves its adsorption efficiency to carbonyl sulfur and its oxygen and sulfur resistance.

Benefits of technology

It significantly improves the activity and life of the catalyst under gas conditions, and achieves efficient removal of carbonyl sulfur in coal gas, with the characteristics of small footprint, high desulfurization accuracy and little impact on the original equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793430A_ABST
    Figure CN119793430A_ABST
Patent Text Reader

Abstract

The invention relates to a hierarchical porous catalyst for carbonyl sulfide hydrolysis and a preparation method and application thereof, and the preparation method of the hierarchical porous catalyst comprises the following steps: (1) mixing a template agent, a solvent, a pore-enlarging agent, an acid solution and an aluminum source to obtain a mixture; (2) sequentially carrying out drying, constant-temperature and constant-humidity standing and heating treatment on the mixture to obtain catalyst powder; and (3) sequentially cooling and granulating the catalyst powder to obtain the hierarchical porous catalyst, the template agent is a polyethylene glycol-polypropylene glycol copolymer. A soft template method is adopted to synthesize the alumina-based catalyst with hierarchical pores for carbonyl sulfide hydrolysis, and the catalyst can realize oxygen resistance and sulfur resistance, so that the activity and the service life of the catalyst under a coal gas working condition are improved, carbonyl sulfide in coal gas can be efficiently removed, and the catalyst has the characteristics of small occupied area, high desulfurization precision and small influence on original equipment and is suitable for industrial production. And the overall technical and economic advantages are very obvious.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coal gas desulfurization / COS hydrolysis, and in particular to a multi-stage pore catalyst for carbonyl sulfide hydrolysis, a preparation method and application thereof. Background Art

[0002] The main components of blast furnace gas include 25-30% CO, 9-12% CO2, 7-10% H2O, 1-4% H2, about 0.3% O2, a small amount of hydrocarbons and sulfur-containing components. The total amount of sulfur-containing components is about 200-300 mg / m 3 , mainly carbonyl sulfide (COS), accounting for about 70-80%, with a concentration of 150-250 mg / m 3 , H2S concentration is 5-50mg / m 3 The rest is carbon disulfide (CS2) and other organic sulfur, about 5 mg / m 3 Therefore, the focus of blast furnace gas desulfurization is the removal of carbonyl sulfide. Common methods include catalytic hydrogenation and catalytic hydrolysis. Catalytic hydrogenation is suitable for high temperature (280-400℃), high concentration (>1000mg / m 3 ), low gas volume (<100,000 Nm 3 / h) gas purification, while the catalytic hydrolysis method is suitable for blast furnace gas conditions (100-150℃, 200,000-600,000 Nm 3 / h) to convert COS into easily treatable H2S and CO2. Blast furnace gas contains a certain amount of water vapor, and no additional water needs to be added as a reactant. The hydrolysis of carbonyl sulfide has significant advantages such as not consuming raw gas, only consuming water in the atmosphere, and having few side reactions.

[0003] The hydrolysis method is used as the treatment process for COS and HCN in blast furnace gas. The reaction formula is as follows:

[0004] COS+H2O=H2S+CO2

[0005] Aluminum-based catalysts are commonly used in the catalytic hydrolysis of COS, but when applied to coal gas, the complex components seriously restrict the activity and life of the catalyst. COS is adsorbed on the alkaline center of the catalyst and reacts with adsorbed H2O to form a thiohydrocarbonate intermediate, which decomposes into H2S and CO2. After desorption, the two enter the gas phase, where a small amount of H2S is oxidized by free oxygen on the catalyst surface or O2 in the atmosphere to elemental sulfur or sulfate deposited on the catalyst surface, resulting in pore blockage and coverage of active sites. The pore structure of the catalyst not only affects the diffusion of the reaction gas and the desorption of the product, but is also a key factor in determining the amount of sulfur deposition. Optimizing the synthesis technology of the hydrolysis catalyst and preparing a catalyst with developed pores is an effective way to increase the life of the catalyst.

[0006] CN115869933A discloses a carbonyl sulfide hydrolysis catalyst and its preparation method and application, wherein the catalyst has aluminum oxide as the main component and the active components include zinc oxide and magnesium oxide. It can achieve efficient hydrolysis, but cannot achieve oxygen and sulfur resistance.

[0007] In summary, it is necessary to develop a multi-stage porous catalyst for carbonyl sulfide hydrolysis that has oxygen and sulfur resistance, so as to improve the activity and life of the catalyst under high space velocity conditions in coal gas conditions, reduce the footprint, and promote the possibility of promoting the process. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a method for preparing a multi-stage porous catalyst. The preparation method can prepare a catalyst with multi-stage pores, which can achieve efficient removal of carbonyl sulfide in coal gas, improve the activity of the multi-stage porous catalyst under coal gas conditions, and extend its service life.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a multi-stage porous catalyst, the preparation method comprising the following steps:

[0011] (1) mixing a template, a solvent, a pore-enlarging agent, an acidic solution, and an aluminum source to obtain a mixture;

[0012] (2) drying, keeping the mixture at a constant temperature and humidity, and heating the mixture in sequence to obtain a catalyst powder;

[0013] (3) sequentially cooling and granulating the catalyst powder to obtain a multi-level porous catalyst;

[0014] The template agent is a polyethylene glycol-polypropylene glycol copolymer.

[0015] The invention uses polyethylene glycol-polypropylene glycol copolymer (Pluronic F-127) as a template agent and adopts a soft template method to prepare an alumina-based catalyst with multi-level pores. The polyethylene glycol-polypropylene glycol copolymer is added to provide a template in the preparation process of the multi-level channel catalyst, so that the multi-level channel catalyst has abundant channels and the size of the pore size is controllable, thereby improving the adsorption efficiency of carbonyl sulfide and promoting the occurrence of carbonyl sulfide hydrolysis reaction; the template agent used is a non-ionic surfactant, which has 100% activity and is relatively non-toxic to cells, and has a long EO block and stronger hydrophilicity, can better form micelles and promote the aggregation of precursors, while other types of template agents are not suitable due to insufficient hydrophilicity and the size of the micelles formed does not meet the requirements. The pore expander is added to expand the pore size of the multi-level channel catalyst. The acidic environment promotes the pore expander to fill the channel, so that the average pore size is increased from the original 6-8nm to about 35nm, accelerating the circulation of gas, and at the same time, the large pore size is conducive to the transportation of deposits on the surface of the multi-level channel catalyst, reducing the influence of O2 and H2S on the carbonyl sulfide hydrolysis reaction, and improving the service life of the multi-level channel catalyst. At the same time, the developed pores can make the multi-stage channel catalyst resistant to oxygen and sulfur. The research and development of oxygen and sulfur resistant catalysts can improve their activity and life under coal gas conditions, increase the space velocity, reduce the footprint, and promote the possibility of promoting the process.

[0016] As a preferred technical solution of the present invention, the solvent includes ethanol.

[0017] Preferably, the mass ratio of the template to the aluminum source is 1:(15-25), for example, it can be 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24 or 1:25, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0018] The present invention limits the mass ratio of the template to the aluminum source to 1:(15-25), so that the prepared multi-stage pore catalyst has abundant pores and the pore size is controllable. If the template is too much, the pore structure will collapse, and if the aluminum source is too much, the pore structure will be chaotic.

[0019] Preferably, the pore expanding agent includes any one of trimethylbenzene, methacrylate or glucose or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of trimethylbenzene and methacrylate, a combination of trimethylbenzene and glucose, a combination of methacrylate and glucose, and a combination of trimethylbenzene, methacrylate and glucose.

[0020] Preferably, the trimethylbenzene is 1,2,3-trimethylbenzene.

[0021] The present invention further prefers that the pore expanding agent is 1,2,3-trimethylbenzene. This is because, compared with other pore expanding agents, the non-polar molecules of 1,2,3-trimethylbenzene can enter the hydrophobic part in the center of the micelle, thereby increasing the diameter of the micelle, thereby increasing the volume of the hydrophobic end of the micelle, and the inorganic matter assembles and condenses on the surface of the micelle, thereby expanding the pore size of the product.

[0022] Preferably, the mass ratio of the pore expanding agent to the aluminum source is 1:(10-15), for example, it can be 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0023] The present invention limits the mass ratio of the pore expanding agent to the aluminum source to 1:(10-15), which can expand the pore size of the multi-stage channel catalyst and make the size of the expanded pore size controllable. If the pore expanding agent is too little, a multi-stage channel catalyst with a larger pore size cannot be formed. If the pore expanding agent is too much, the channel structure will collapse.

[0024] As a preferred technical solution of the present invention, the acidic solution includes organic acid and / or inorganic acid, preferably a combination of organic acid and inorganic acid.

[0025] Preferably, the mass ratio of the acid in the acidic solution to the pore expanding agent is 1:(8-10), for example, it can be 1:8, 1:8.5, 1:9, 1:9.5 or 1:10, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0026] In the preparation process of the multi-level channel catalyst, an acidic solution is added thereto, and the mass ratio of the acid in the acidic solution to the pore-enlarging agent is limited to 1:(8-10), and the pH of the system is adjusted to 4.6-5.4. The acidic environment is an ideal environment for the pore-enlarging agent to fill the pores, and the average pore diameter of the multi-level channel catalyst can be increased from the original 6-8nm to about 35nm. If the acidity is too strong, the formed alumina multi-level channel catalyst will be decomposed. If the acidity is too weak, the template agent cannot be eliminated, resulting in the template agent remaining in the formed multi-level channel catalyst and low activity.

[0027] Preferably, the organic acid comprises any one of formic acid, acetic acid, malic acid, citric acid or salicylic acid, or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of formic acid and acetic acid, a combination of formic acid and malic acid, a combination of formic acid and citric acid, a combination of formic acid and salicylic acid, a combination of acetic acid and malic acid, a combination of acetic acid and citric acid, a combination of acetic acid and salicylic acid, a combination of malic acid and citric acid, a combination of malic acid and salicylic acid, a combination of citric acid and salicylic acid, a combination of formic acid, acetic acid and malic acid, a combination of formic acid, acetic acid and citric acid, a combination of formic acid, acetic acid and salicy ... A combination of fruit acid and citric acid, a combination of formic acid, malic acid and salicylic acid, a combination of formic acid, citric acid and salicylic acid, a combination of acetic acid, malic acid and citric acid, a combination of acetic acid, malic acid and salicylic acid, a combination of acetic acid, citric acid and salicylic acid, a combination of malic acid, citric acid and salicylic acid, a combination of formic acid, acetic acid, malic acid and citric acid, a combination of formic acid, acetic acid, malic acid and salicylic acid, a combination of formic acid, acetic acid, citric acid and salicylic acid, a combination of formic acid, malic acid, citric acid and salicylic acid, a combination of acetic acid, malic acid, citric acid and salicylic acid, a combination of formic acid, acetic acid, malic acid, citric acid and salicylic acid.

[0028] Preferably, the inorganic acid comprises any one of sulfuric acid, hydrochloric acid, carbonic acid or nitric acid, or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of sulfuric acid and hydrochloric acid, a combination of sulfuric acid and carbonic acid, a combination of sulfuric acid and nitric acid, a combination of hydrochloric acid and carbonic acid, a combination of hydrochloric acid and nitric acid, a combination of carbonic acid and nitric acid, a combination of sulfuric acid, hydrochloric acid and carbonic acid, a combination of sulfuric acid, hydrochloric acid and nitric acid, a combination of sulfuric acid, carbonic acid and nitric acid, a combination of hydrochloric acid, carbonic acid and nitric acid, and a combination of sulfuric acid, hydrochloric acid, carbonic acid and nitric acid.

[0029] Preferably, the aluminum source comprises aluminum isopropoxide or aluminum n-butoxide.

[0030] Preferably, the particle size of the aluminum source is 0.5-1 mm, for example, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0031] Preferably, the molecular weight of the polyethylene glycol-polypropylene glycol copolymer is 12000-15000, for example, 12000, 12700, 13400, 14500 or 15000, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0032] The present invention limits the length and molecular weight of the polyethylene glycol-polypropylene glycol copolymer. This is because if the molecular weight is too low, the hydrophilicity of the template is insufficient, micelles are difficult to produce, and it is difficult to form the target structure; if the molecular weight is too high, the hydrophilicity of the template is too high, resulting in prolonged heating time and the structure of the formed multi-stage channel catalyst is prone to deformation.

[0033] As a preferred technical solution of the present invention, the mixing in step (1) includes: adding the template to the solvent and stirring to obtain a mixed solution; premixing the mixed solution with the pore expanding agent to obtain a premix; and sequentially adding an acidic solution and an aluminum source to the premix.

[0034] The present invention limits the order of mixing the components. This is because the template agent is first added to provide a template for the preparation of the multi-level channel catalyst, so that the multi-level channel catalyst has abundant channels and the size of the pores is controllable. Then, the pore expander is added to expand the pore size of the multi-level channel catalyst. The acidic solution is then added because the acidic environment can promote the pore expander to fill the channels.

[0035] Preferably, the stirring speed is 300-400r / min, and the stirring time is 0.5-1.5h. The stirring speed may be 300r / min, 320r / min, 340r / min, 360r / min, 380r / min or 400r / min, and the stirring time may be 0.5h, 0.7h, 0.9h, 1.1h, 1.3h or 1.5h, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0036] Preferably, the premixing speed is 100-150r / min, and the premixing time is 14-19h. The premixing speed may be 100r / min, 110r / min, 120r / min, 130r / min, 140r / min or 150r / min, and the premixing time may be 14h, 15h, 16h, 17h, 18h or 19h, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0037] Preferably, the drying temperature is 45-55°C, for example, 45°C, 47°C, 49°C, 51°C, 53°C or 55°C, but is not limited to the listed values, and other unlisted values ​​within the above range are also applicable.

[0038] Preferably, the drying time is 40-60 h, for example, 40 h, 45 h, 50 h, 55 h or 60 h, but is not limited to the listed values, and other values ​​not listed within the above range are also applicable.

[0039] Preferably, the stacking thickness of the mixture during the drying process is 4-10 cm, for example, 4 cm, 5 cm, 6 cm, 7 cm, 8 cm, 9 cm or 10 cm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0040] In the drying process of the present invention, air is used to circulate and dry the mixture, and the circulation flow rate of the air is 3-5 L / min, for example, it can be 3 L / min, 3.5 L / min, 4 L / min, 4.5 L / min or 5 L / min, but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0041] As a preferred technical solution of the present invention, the temperature of the constant temperature and humidity static treatment is 35-45°C, for example, it can be 35°C, 37°C, 39°C, 41°C, 43°C or 45°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0042] Preferably, the relative humidity of the constant temperature and humidity static treatment is 5-8%, for example, it can be 5%, 6%, 7% or 8%, but it is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0043] The present invention stipulates that the mixture needs to be placed in a constant temperature and humidity environment after being dried, because a constant temperature and humidity environment is conducive to the growth of the pore structure of the multi-level channel catalyst.

[0044] Preferably, the constant temperature and humidity static treatment time is 144-192 hours, for example, it can be 144 hours, 156 hours, 168 hours, 180 hours or 192 hours, but it is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0045] Preferably, the stacking thickness of the mixture during the constant temperature and humidity static treatment is 5-10 cm, for example, it can be 5 cm, 6 cm, 7 cm, 8 cm, 9 cm or 10 cm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0046] During the constant temperature and humidity static process of the present invention, air is used to circulate the mixture to ensure constant temperature and humidity, and the circulation rate of the air is 3-5L / min, for example, it can be 3L / min, 3.5L / min, 4L / min, 4.5L / min or 5L / min, but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0047] As a preferred technical solution of the present invention, the heating treatment includes heating and heat preservation performed sequentially.

[0048] Preferably, the heating rate is 50-70°C / h, for example, 50°C / h, 55°C / h, 60°C / h, 65°C / h or 70°C / h, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0049] Preferably, the target temperature of the heating is 680-720°C, for example, 680°C, 690°C, 700°C, 710°C or 720°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0050] Preferably, the insulation time is 5-8h, for example, it can be 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 8h, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0051] Preferably, the atmosphere for the heat treatment comprises any one of nitrogen, argon or helium, or a combination of at least two of them, wherein typical but non-limiting combinations include: a combination of nitrogen and argon, a combination of nitrogen and helium, a combination of argon and helium, and a combination of nitrogen, argon and helium.

[0052] Preferably, the target temperature of the cooling is 20-25°C, for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C or 25°C, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0053] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0054] (1) dissolving a polyethylene glycol-polypropylene glycol copolymer in a solvent, and stirring the mixture at a speed of 300-400 r / min for 0.5-1.5 h to obtain a mixed solution;

[0055] (2) premixing the mixed solution with a pore expanding agent at a rotation speed of 100-150 r / min to obtain a premix, adding an acidic solution to the premix and stirring for 15-45 min, adjusting the pH to 4.6-5.4, and then adding an aluminum source to the premix to obtain a mixture;

[0056] (3) drying the mixture at 45-55° C. for 40-60 h; then allowing the mixture to stand at a temperature of 35-45° C. and a relative humidity of 5-8% for 144-192 h; then heating the mixture to 680-720° C. at a rate of 50-70° C. / h and keeping the temperature for 5-8 h to obtain a catalyst powder;

[0057] (4) Cooling the catalyst powder to 20-25° C. and granulating the powder to obtain a multi-level channel catalyst.

[0058] In a second aspect, the present invention provides a multi-level pore catalyst prepared according to the preparation method described in the first aspect, wherein the multi-level pore catalyst has both macroporous channels and mesoporous channels.

[0059] The multi-level channel catalyst prepared by the present invention has abundant macropore channels and mesopore channels, and the pore size is controllable. It has a good adsorption effect on carbonyl sulfide and can promote the occurrence of carbonyl sulfide hydrolysis reaction. At the same time, the large pore size is conducive to the transportation of deposits on the surface of the multi-level channel catalyst, reduces the influence of O2 and H2S on the hydrogen sulfide hydrolysis reaction, and improves the service life of the multi-level channel catalyst, so that the multi-level channel catalyst has oxygen and sulfur resistance characteristics.

[0060] As a preferred technical solution of the present invention, the pore size of the macropore channel is 100-200nm, for example, it can be 100nm, 120nm, 140nm, 160nm, 180nm or 200nm, but it is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0061] Preferably, the pore size of the mesoporous channel is 2-50 nm, for example, 2 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm or 50 nm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0062] The present invention prepares a multi-level pore catalyst having both macropores and mesopores, and the pore size of the macropores is 100-200nm, and the pore size of the mesopores is 2-50nm, which can promote the diffusion of gas molecules and improve the combination efficiency of gas molecules and active components.

[0063] Preferably, the particle size of the multi-stage porous catalyst is 3-5 mm, for example, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0064] Preferably, the specific surface area of ​​the multi-stage pore catalyst is 300-450m 2 / g, for example, 300m 2 / g, 350m 2 / g, 380m 2 / g, 400m 2 / g or 450m 2 / g, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0065] The present invention prepares a specific surface area of ​​300-450m 2 / g of multi-level pore catalyst can promote the diffusion of gas molecules and increase the contact area between gas molecules and catalyst.

[0066] Preferably, the porosity of the multi-stage porous catalyst is 60-70%, for example, 60%, 63%, 65%, 68% or 70%, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0067] The multi-level channel catalyst with a porosity of 60-70% prepared by the invention can improve the diffusion rate of gas molecules.

[0068] Preferably, the shape of the multi-stage porous catalyst includes any one of sphere, bar or cylinder, or a combination of at least two of them, wherein typical but non-limiting combinations include: a combination of sphere and bar, a combination of sphere and cylinder, a combination of bar and cylinder, and a combination of sphere, bar and cylinder.

[0069] In a third aspect, the present invention provides a use of a multi-stage pore catalyst obtained according to the preparation method described in the first aspect in the hydrolysis of carbonyl sulfide.

[0070] The main components of blast furnace gas include 25-30% CO, 9-12% CO2, 7-10% H2O, 1-4% H2, about 0.3% O2, a small amount of hydrocarbons and sulfur-containing components. The sulfur in the gas is an important factor causing pipeline corrosion. After removal, the corrosion and blockage of the pipeline are effectively slowed down. The multi-stage pore catalyst obtained by the preparation method according to the first aspect of the present invention has macropore channels and mesopore channels. At an air velocity of 3000-5000h -1 Under the condition of , it is still possible to achieve efficient removal of carbonyl sulfide in coal gas. It has the characteristics of small footprint, high desulfurization accuracy and small impact on original equipment. The overall technical and economic advantages are very obvious.

[0071] Compared with the prior art, the present invention has at least the following beneficial effects:

[0072] (1) The preparation method of the multi-level porous catalyst provided by the present invention can prepare a multi-level porous catalyst having macroporous channels and mesoporous channels, so that the catalyst has oxygen and sulfur resistance characteristics, and can improve the activity and life of the catalyst under coal gas conditions. The prepared multi-level porous catalyst is used to hydrolyze blast furnace gas, and its initial hydrolysis reaction activity can reach more than 95%, and its service life can reach more than 10 months. After three months of hydrolysis, the activity reduction rate of the multi-level porous catalyst is less than 15%, which solves the problem that the catalyst does not have oxygen and sulfur resistance characteristics and has a short life;

[0073] (2) The prepared multi-stage porous catalyst can achieve efficient removal of carbonyl sulfide in coal gas. It has the characteristics of small footprint, high desulfurization accuracy, and little impact on the original equipment. The overall technical and economic advantages are very obvious. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 The present invention is a flow chart of the method for preparing the multi-stage porous catalyst.

[0075] Figure 2 This is a SEM image of the multi-stage porous catalyst prepared in Example 1 of the present invention.

[0076] Figure 3 This is a TEM image of the multi-level porous catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0077] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0078] The following examples and comparative examples provide a flow chart of the preparation method of the multi-stage pore catalyst. Figure 1 As shown, a detailed description is given below.

[0079] Example 1

[0080] This embodiment provides a method for preparing a multi-stage pore catalyst, the preparation method comprising the following steps:

[0081] (1) dissolving a polyethylene glycol-polypropylene glycol copolymer in ethanol and stirring at a rotation speed of 350 r / min for 1 h to obtain a mixed solution;

[0082] Among them, the molecular weight of polyethylene glycol-polypropylene glycol copolymer is 12600, and the length of polyethylene glycol-polypropylene glycol copolymer is (PEO) 106 (PPO) 70 (PEO) 106 ;

[0083] (2) premixing the mixed solution with 1,2,3-trimethylbenzene at a speed of 120 r / min for 16 hours to obtain a premix, adding a citric acid solution and a hydrochloric acid solution to the premix, and stirring for 30 minutes, wherein the amount of citric acid added to the citric acid solution is 1%, and the amount of hydrochloric acid added to the 38% hydrochloric acid solution is 0.6%, adjusting the pH to 5, and then adding aluminum isopropoxide to the premix to obtain a mixture;

[0084] The mass ratio of polyethylene glycol-polypropylene glycol copolymer, 1,2,3-trimethylbenzene, citric acid (in pure form), hydrochloric acid (in pure form) and aluminum isopropoxide is 4:9:0.4:0.6:100, and the particle size of aluminum isopropoxide is 0.8 mm.

[0085] (3) drying the mixture at 50° C. for 50 h, during which the stacking thickness of the mixture was 6 cm; then allowing the mixture to stand at 40° C. and 5% relative humidity for 168 h, during which the stacking thickness of the mixture was 7 cm; then heating the mixture to 700° C. at a rate of 60° C. / h in a nitrogen atmosphere, and keeping the temperature for 6 h, to obtain a catalyst powder;

[0086] (4) The catalyst powder is cooled to 22° C. and granulated to obtain a multi-level channel catalyst.

[0087] The structure of the multi-level pore catalyst is as follows Figure 2 and 3 The multi-level pore catalyst has both macropores and mesopores, the pore size of the macropores is 150nm; the pore size of the mesopores is 25nm; the multi-level pore catalyst is spherical, with a particle size of 4mm and a specific surface area of ​​350m 2 / g, porosity is 65%.

[0088] Example 2

[0089] This embodiment provides a method for preparing a multi-stage pore catalyst, the preparation method comprising the following steps:

[0090] (1) dissolving a polyethylene glycol-polypropylene glycol copolymer in ethanol and stirring the mixture at a speed of 300 r / min for 1.5 h to obtain a mixed solution;

[0091] Wherein, the molecular weight of polyethylene glycol-polypropylene glycol copolymer is 12000;

[0092] (2) premixing the mixed solution with glucose at a speed of 100 r / min for 19 hours to obtain a premix, adding a salicylic acid solution and a nitric acid solution to the premix, and stirring for 15 minutes, wherein the amount of salicylic acid added to the salicylic acid solution is 1%, and the amount of nitric acid added to the fuming nitric acid solution is 0.6%, adjusting the pH to 4.6, and then adding aluminum n-butoxide to the premix to obtain a mixture;

[0093] The mass ratio of polyethylene glycol-polypropylene glycol copolymer, glucose, salicylic acid (in pure form), nitric acid (in pure form) and aluminum n-butoxide is 10:10:0.3:0.7:150, and the particle size of aluminum n-butoxide is 0.5 mm.

[0094] (3) drying the mixture at 55° C. for 40 h, wherein the stacking thickness of the mixture during the drying process is 10 cm; then allowing the mixture to stand at a temperature of 35° C. and a relative humidity of 8% for 192 h, wherein the stacking thickness of the mixture during the standing process is 5 cm; then heating the mixture to 680° C. at a rate of 50° C. / h in a nitrogen atmosphere, and maintaining the temperature for 5 h, to obtain a catalyst powder;

[0095] (4) The catalyst powder is cooled to 20° C. and granulated to obtain a multi-level porous catalyst.

[0096] The multi-level pore catalyst has both macropores and mesopores, the pore size of the macropores is 100nm; the pore size of the mesopores is 2nm; the multi-level pore catalyst is spherical, with a particle size of 5mm and a specific surface area of ​​450m 2 / g, porosity is 70%.

[0097] Example 3

[0098] This embodiment provides a method for preparing a multi-stage pore catalyst, the preparation method comprising the following steps:

[0099] (1) dissolving a polyethylene glycol-polypropylene glycol copolymer in ethanol and stirring at a speed of 400 r / min for 0.5 h to obtain a mixed solution;

[0100] Wherein, the molecular weight of polyethylene glycol-polypropylene glycol copolymer is 15000;

[0101] (2) premixing the mixed solution with methacrylate at a rotation speed of 150 r / min for 14 hours to obtain a premix, adding a formic acid solution and a carbonic acid solution to the premix, and stirring for 45 minutes, wherein the amount of formic acid added to the formic acid solution is 1%, and the amount of the carbonic acid solution added is 1%, and the pH is adjusted to 5.4, and then adding aluminum isopropoxide to the premix to obtain a mixture;

[0102] The mass ratio of polyethylene glycol-polypropylene glycol copolymer, methacrylate, formic acid (in pure form), carbonic acid (in pure form) and aluminum isopropoxide is 8:16:1:1:160, and the particle size of aluminum isopropoxide is 1 mm.

[0103] (3) drying the mixture at 45° C. for 60 h, wherein the stacking thickness of the mixture during the drying process is 4 cm; then allowing the mixture to stand at 45° C. and 6% relative humidity for 144 h, wherein the stacking thickness of the mixture during the standing process is 10 cm; then heating the mixture at a rate of 70° C. / h to 720° C. in a nitrogen atmosphere, and keeping the temperature for 8 h, to obtain a catalyst powder;

[0104] (4) The catalyst powder is cooled to 25° C. and granulated to obtain a multi-level porous catalyst.

[0105] The multi-level pore catalyst has both macropores and mesopores, the pore size of the macropores is 200nm; the pore size of the mesopores is 50nm; the multi-level pore catalyst is spherical, with a particle size of 3mm and a specific surface area of ​​350m 2 / g, porosity is 60%.

[0106] Example 4

[0107] This embodiment provides a method for preparing a multi-stage pore catalyst, which is different from the embodiment 1 only in that the mass ratio of polyethylene glycol-polypropylene glycol copolymer to aluminum isopropoxide is adjusted to 1:10, that is, the template agent polyethylene glycol-polypropylene glycol copolymer is added more, and the rest is the same as the embodiment 1. The catalyst prepared in this embodiment has only macroporous channels, and the average pore size of the channels is 200nm; it is not a multi-stage pore catalyst, but a macroporous catalyst with a specific surface area of ​​200m 2 / g, porosity is 90%.

[0108] Example 5

[0109] This embodiment provides a method for preparing a multi-stage pore catalyst, which is different from the embodiment 1 only in that the mass ratio of polyethylene glycol-polypropylene glycol copolymer to aluminum isopropoxide is adjusted to 1:100, that is, the addition of the template agent polyethylene glycol-polypropylene glycol copolymer is slightly less, and the rest is the same as the embodiment 1. The catalyst prepared in this embodiment has only mesoporous channels, and the pore size of the mesoporous channels is 10nm; the non-multi-stage pore catalyst has a specific surface area of ​​300m 2 / g, porosity is 40%.

[0110] Example 6

[0111] This embodiment provides a method for preparing a multi-stage pore catalyst, which is different from the embodiment 1 only in that the mass ratio of 1,2,3-trimethylbenzene to aluminum isopropoxide is adjusted to 1:5, that is, the pore-enlarging agent 1,2,3-trimethylbenzene is added more, and the rest is the same as the embodiment 1. The catalyst prepared in this embodiment has both macropores and mesopores, with an average pore diameter of 50nm. The multi-stage pore catalyst is spherical with a specific surface area of ​​350m 2 / g, porosity is 40%.

[0112] Example 7

[0113] This embodiment provides a method for preparing a multi-stage pore catalyst, which is different from the embodiment 1 only in that the mass ratio of 1,2,3-trimethylbenzene to aluminum isopropoxide is adjusted to 1:20, that is, the amount of pore-enlarging agent 1,2,3-trimethylbenzene added is slightly less, and the rest is the same as the embodiment 1. The catalyst prepared in this embodiment has only mesoporous channels, and the pore size of the mesoporous channels is 25nm; the non-multi-stage pore catalyst has a specific surface area of ​​280m 2 / g, porosity is 30%.

[0114] Example 8

[0115] This embodiment provides a method for preparing a multi-stage pore catalyst, which is different from the embodiment 1 only in that the mass ratio of 1,2,3-trimethylbenzene, citric acid, and hydrochloric acid is 12:5:3, that is, the acid is added in a larger amount, and the pH of the premixture is adjusted to 4 after the acid is added, and the rest is the same as the embodiment 1. The catalyst prepared in this embodiment has only mesoporous channels, and the pore size of the mesoporous channels is 10nm; the non-multi-stage pore catalyst has a specific surface area of ​​180m 2 / g, porosity is 30%.

[0116] Example 9

[0117] This embodiment provides a method for preparing a multi-stage pore catalyst, which is different from the embodiment 1 only in that the mass ratio of 1,2,3-trimethylbenzene, citric acid, and hydrochloric acid is 12:0.7:0.3, that is, the acid is added less, and the pH of the premixture is adjusted to 6 after adding the acidic solution. The rest is the same as the embodiment 1. The catalyst prepared in this embodiment has both macroporous channels and mesoporous channels, and the average pore size of the channels is 30nm; the multi-stage pore catalyst is spherical, with a specific surface area of ​​280m 2 / g, porosity is 50%.

[0118] Comparative Example 1

[0119] This comparative example provides a method for preparing a multi-level channel catalyst, which is different from Example 1 only in that, except that the template agent is adjusted from polyethylene glycol-polypropylene glycol copolymer to polyethylene oxide triblock copolymer (molecular weight is 5400), the rest is the same as Example 1. The catalyst prepared in this comparative example has both macroporous channels and mesoporous channels, and the average pore size of the channels is 30nm; the multi-level channel catalyst is spherical, with a specific surface area of ​​300m 2 / g, porosity is 50%.

[0120] Comparative Example 2

[0121] This comparative example provides a method for preparing a multi-level channel catalyst, which is different from Example 1 only in that, except that the template agent is adjusted from polyethylene glycol-polypropylene glycol copolymer to polyethylene glycol-polybutylene glycol copolymer (molecular weight is 20000), the rest is the same as Example 1. The catalyst prepared in this comparative example has only mesoporous channels, and the pore size of the mesoporous channels is 15nm; the multi-level channel catalyst is spherical, and the specific surface area is 150m 2 / g, and the porosity is 30%.

[0122] Comparative Example 3

[0123] This comparative example provides a method for preparing a multi-stage pore catalyst, which is different from Example 1 only in that, except that the citric acid solution and the hydrochloric acid solution are replaced by water of the same mass, the rest is the same as Example 1. The catalyst prepared in this comparative example has only mesoporous channels, and the pore size of the mesoporous channels is 10nm; the non-multi-stage pore catalyst has a specific surface area of ​​180m 2 / g, porosity is 30%.

[0124] Comparative Example 4

[0125] This comparative example provides a method for preparing a multi-stage pore catalyst, which is different from Example 1 only in that, except that the mixture does not include the pore-enlarging agent 1,2,3-trimethylbenzene, the rest is the same as Example 1. The catalyst prepared in this comparative example has only mesoporous channels, and the pore diameter of the mesoporous channels is 10nm; the non-multi-stage pore catalyst has a specific surface area of ​​150m 2 / g, and the porosity is 30%.

[0126] Comparative Example 5

[0127] This comparative example provides a method for preparing a multi-level porous catalyst, which is different from Example 1 only in that, except that the mixture is directly heated instead of being placed at a constant temperature and humidity after drying, the rest is the same as Example 1. The catalyst prepared in this comparative example has both macroporous channels and mesoporous channels, and the average pore size of the channels is 25 nm; the multi-level porous catalyst is spherical, with a specific surface area of ​​300 m 2 / g, and the porosity is 40%.

[0128] Comparative Example 6

[0129] This comparative example provides a commercial alumina catalyst (brand name EH-4), which has both macropores and mesopores, and the average pore size of the pores is 25nm; the multi-stage pore catalyst is spherical, with a particle size of 5mm and a specific surface area of ​​200m 2 / g, porosity is 50%.

[0130] In a steel plant in Tangshan, 3000m 3 The catalysts in the above embodiments and comparative examples were tested in a blast furnace with a blast furnace gas temperature of 120°C, a pressure of 250 kPa, and a space velocity of 4000 h -1 The inlet COS concentration is 150mg / m 3 The concentration of COS is detected by gas chromatography (Shimadzu 2010plus). The main components of blast furnace gas include 25-30% CO, 9-12% CO2, 7-10% H2O, 1-4% H2, about 0.3% O2, a small amount of hydrocarbons and sulfur-containing components. The total amount of sulfur-containing components is about 200-300 mg / m 3 .

[0131] The service life of the catalyst is the time during which the hydrolysis efficiency of the catalyst in hydrolyzing carbonyl sulfide is greater than 90%; the activity reduction rate of the catalyst = (catalyst activity of the initial hydrolysis reaction - catalyst activity three months after the hydrolysis reaction) / catalyst activity of the initial hydrolysis reaction, wherein the catalyst activity refers to the ratio of the actual conversion rate of the reactants per unit time in the hydrolysis reaction to the theoretical conversion rate.

[0132] According to the above test method and calculation formula, the service life of the catalyst, the catalyst activity of the initial hydrolysis reaction and the activity reduction rate are obtained. The test results are shown in Table 1.

[0133] Table 1

[0134] Service life (month) Catalyst activity of initial hydrolysis reaction (%) Activity reduction rate (%) Example 1 12 99 10 Example 2 10 95 15 Example 3 10 95 15 Example 4 8 95 20 Example 5 7 90 25 Example 6 9 90 20 Example 7 6 80 30 Example 8 4 70 40 Example 9 6 75 35 Comparative Example 1 8 80 30 Comparative Example 2 4 60 30 Comparative Example 3 4 60 35 Comparative Example 4 3 60 35 Comparative Example 5 6 70 40 Comparative Example 6 3 70 45

[0135] The test results show that:

[0136] (1) It can be seen from Examples 1-3 that the present invention uses polyethylene glycol-polypropylene glycol copolymer as a template agent and adopts a soft template method to prepare an alumina-based catalyst with multi-level pores. The addition of polyethylene glycol-polypropylene glycol copolymer is to provide a template in the preparation process of the multi-level pore catalyst, so that the multi-level pore catalyst has abundant pores and the size of the pore size is controllable, thereby improving the adsorption efficiency of carbonyl sulfide and promoting the occurrence of carbonyl sulfide hydrolysis reaction; the addition of the pore expander is to expand the pore size of the multi-level pore catalyst. The acidic environment promotes the filling of the pore expander into the pore. The large pore size is conducive to accelerating the flow of gas. At the same time, the large pore size is conducive to the transportation of deposits on the surface of the multi-level pore catalyst, reducing the influence of O2 and H2S on the carbonyl sulfide hydrolysis reaction, and improving the service life of the multi-level pore catalyst. The activity of the prepared multi-level pore catalyst in the initial hydrolysis reaction can reach more than 95%, and its service life can reach more than 10 months. After three months of hydrolysis, the activity reduction rate of the multi-level pore catalyst is less than 15%.

[0137] (2) Combining Example 1 and Examples 4-5, it can be seen that the mass ratio of the polyethylene glycol-polypropylene glycol copolymer used in Example 1 to aluminum isopropoxide is 1:25. Example 1 prepares a multi-stage pore catalyst having both macropores and mesopores, and its specific surface area is 350 m 2 / g, porosity of 65%, initial hydrolysis reaction catalyst activity of 99%, service life of up to 12 months, three months after hydrolysis, the activity reduction rate of the multi-stage channel catalyst was 10%, and the mass ratio of the polyethylene glycol-polypropylene glycol copolymer to aluminum isopropoxide used in Example 4 was 1:10, and the catalyst prepared therefrom had only macroporous channels, and its specific surface area was 200m 2 / g, porosity is 90%, the catalyst activity of the initial hydrolysis reaction is 95%, the service life is 8 months, and the activity reduction rate of the multi-stage pore catalyst after three months of hydrolysis is 20%; the mass ratio of the polyethylene glycol-polypropylene glycol copolymer used in Example 5 to aluminum isopropoxide is 1:100, and the catalyst prepared therefrom has only mesoporous channels, and its specific surface area is 300m 2 / g, porosity is 40%, catalyst activity of the initial hydrolysis reaction is 90%, service life is 7 months, and activity reduction rate of the multi-level pore catalyst after three months of hydrolysis is 25%. This indicates that the present invention limits the mass ratio of template to aluminum source to 1:(15-25), so that the prepared multi-level pore catalyst has abundant pores and controllable pore size. Too much template will lead to collapse of the pore structure, and too much aluminum source will lead to disorder of the pore structure.

[0138] (3) It can be seen from Example 1 and Examples 6-7 that the mass ratio of 1,2,3-trimethylbenzene to aluminum isopropoxide used in Example 1 is 9:100. The multi-stage pore catalyst having both macropores and mesopores is prepared in Example 1, and its specific surface area is 350 m 2 / g, porosity of 65%, initial hydrolysis reaction catalyst activity of 99%, service life of up to 12 months, three months after hydrolysis, the activity reduction rate of the multi-stage channel catalyst was 10%, and the mass ratio of 1,2,3-trimethylbenzene to aluminum isopropoxide used in Example 6 was 1:5. Although the prepared catalyst had both macroporous channels and mesoporous channels, its porosity was 40%, initial hydrolysis reaction catalyst activity of 90%, service life of 9 months, and three months after hydrolysis, the activity reduction rate of the multi-stage channel catalyst was 20%; the mass ratio of 1,2,3-trimethylbenzene to aluminum isopropoxide used in Example 7 was 1:20, and the prepared catalyst had only mesoporous channels, and its specific surface area was 280m 2 / g, porosity is 30%, the catalyst activity of the initial hydrolysis reaction is only 80%, the service life is 6 months, and the activity reduction rate of the multi-stage channel catalyst after three months of hydrolysis is 30%. This shows that the present invention limits the mass ratio of the pore expander to the aluminum source to 1: (10-15), which can expand the pore size of the multi-stage channel catalyst and make the size of the expanded pore size controllable. If the pore expander is too little, a multi-stage channel catalyst with a larger pore size cannot be formed, and too much pore expander will cause the channel structure to collapse.

[0139] (4) Combining Example 1 and Examples 8-9, it can be seen that the mass ratio of 1,2,3-trimethylbenzene, citric acid, and hydrochloric acid used in Example 1 is 9:0.4:0.6. Example 1 prepares a multi-stage pore catalyst having both macropores and mesopores, and its specific surface area is 350 m 2 / g, porosity is 65%, the catalyst activity of the initial hydrolysis reaction is 99%, the service life can reach 12 months, and the activity reduction rate of the multi-stage pore catalyst after three months of hydrolysis is 10%. The mass ratio of 1,2,3-trimethylbenzene, citric acid and hydrochloric acid used in Example 8 is 12:5:3, and the prepared catalyst has only mesoporous channels, and its specific surface area is 180m 2 / g, porosity of 30%, initial hydrolysis reaction catalyst activity of 70%, service life of only 4 months, three months after hydrolysis, the activity reduction rate of the multi-stage pore catalyst was 40%; the mass ratio of 1,2,3-trimethylbenzene, citric acid and hydrochloric acid used in Example 9 was 12:0.7:0.3. Although the prepared catalyst had both macroporous and mesoporous channels, its specific surface area was 280m 2 / g, porosity is 50%, the catalyst activity of the initial hydrolysis reaction is only 75%, the service life is 6 months, and the activity reduction rate of the multi-level channel catalyst after three months of hydrolysis is 35%. This shows that the present invention limits the mass ratio of acid to pore expander in the acidic solution to 1: (8-10), and adjusts the pH of the system to 4.6-5.4, so that the average pore size of the multi-level channel catalyst can be increased from the original 6-8nm to about 35nm. If the acidity is too strong, the formed alumina multi-level channel catalyst will decompose. If the acidity is too weak, the template agent cannot be eliminated, resulting in the formation of the multi-level channel catalyst with residual template agent and low activity.

[0140] (5) It can be seen from Example 1 and Comparative Examples 1-2 that the template used in Comparative Example 1 is a polyethylene oxide triblock copolymer (molecular weight of 5400). Although the catalyst prepared therefrom has both macroporous channels and mesoporous channels, its specific surface area is 300 m 2 / g, porosity is 50%, the catalyst activity of the initial hydrolysis reaction is only 80%, the service life is 8 months, and the activity reduction rate of the multi-stage channel catalyst after three months of hydrolysis is 30%. The template used in Comparative Example 2 is polyethylene glycol-polybutylene glycol copolymer (molecular weight is 20000), and the catalyst prepared therefrom has only mesoporous channels, and its specific surface area is 150m 2 / g, porosity is 30%, the catalyst activity of the initial hydrolysis reaction is only 60%, the service life is 4 months, and the activity reduction rate of the multi-level pore catalyst after three months of hydrolysis is 30%, which shows that the present invention limits the polyethylene glycol-polypropylene glycol copolymer as a template agent, and adopts a soft template method to prepare an alumina-based catalyst with multi-level pores. The polyethylene glycol-polypropylene glycol copolymer is a non-ionic surfactant, which has 100% activity and is relatively non-toxic to cells, and the EO block is long and more hydrophilic, which can better form micelles and promote the aggregation of precursors. Therefore, the prepared multi-level pore catalyst has abundant pores and the pore size is controllable, thereby improving the adsorption efficiency of carbonyl sulfide and promoting the occurrence of carbonyl sulfide hydrolysis reaction.

[0141] (6) It can be seen from Example 1 and Comparative Example 3 that Comparative Example 3 does not provide an acidic environment for the pore-enlarging agent, and the catalyst prepared therefrom has only mesoporous channels, and its specific surface area is 180 m 2 / g, porosity is 30%, catalyst activity of the initial hydrolysis reaction is only 60%, service life is 4 months, and the activity reduction rate of the multi-level channel catalyst after three months of hydrolysis is 35%. This shows that the acidic environment can promote the pore expander to fill into the pores, increase its average pore diameter, and accelerate the flow of gas. At the same time, the large pore diameter is conducive to the transportation of deposits on the surface of the multi-level channel catalyst, reducing the influence of O2 and H2S on the carbonyl sulfide hydrolysis reaction and improving the service life of the multi-level channel catalyst.

[0142] (7) It can be seen from Example 1 and Comparative Example 4 that in the preparation process of the catalyst in Comparative Example 4, no pore expanding agent was used, and the catalyst prepared therefrom only had mesoporous channels with a pore diameter of 10 nm, while the catalyst prepared in Example 1 had both macroporous channels and mesoporous channels, with the pore diameter of the macroporous channels being 150 nm and the pore diameter of the mesoporous channels being 25 nm. This indicates that the addition of a pore expanding agent can expand the pore diameter of the multi-stage channel catalyst.

[0143] (8) It can be seen from Example 1 and Comparative Example 5 that the mixture in Comparative Example 5 was directly heated after drying without being placed in a constant temperature and humidity state. The obtained catalyst has both macroporous and mesoporous channels, but its average pore diameter is 25 nm and its specific surface area is 300 m 2 / g, porosity is 40%, the catalyst activity of the initial hydrolysis reaction is only 70%, the service life is 6 months, and the activity reduction rate of the multi-level channel catalyst after three months of hydrolysis is 40%. This shows that a constant temperature and humidity environment is conducive to the growth of the pore structure of the multi-level channel catalyst.

[0144] (9) It can be seen from Example 1 and Comparative Example 6 that the catalyst used in Example 6 is a commercial alumina catalyst (brand name: EH-4), which has both macropores and mesopores, but its catalyst activity in the initial hydrolysis reaction is only 70%, and its service life is 3 months. After three months of hydrolysis, the activity reduction rate of the multi-stage pore catalyst is 45%, that is, the service life and catalyst activity test data of the multi-stage pore catalyst prepared by the preparation method defined in the present invention are better than those of the commercial alumina catalyst. The multi-stage pore catalyst prepared by the present invention can improve its activity and life under coal gas conditions, and can achieve efficient removal of carbonyl sulfide in coal gas.

[0145] In summary, the present invention adopts a soft template method to synthesize an alumina-based catalyst with multi-level pores, optimizes the void structure of the catalyst, and the catalyst has macropores and mesopores. At the same time, the adsorption performance and selectivity of the gas are improved, and it can be used for the hydrolysis of carbonyl sulfide. The catalyst can achieve oxygen and sulfur resistance, thereby improving its activity and life under coal gas conditions, and can achieve efficient removal of carbonyl sulfide in coal gas. It has the characteristics of small footprint, high desulfurization accuracy, and small impact on original equipment. The overall technical and economic advantages are very obvious, which promotes the possibility of popularizing the process.

[0146] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a multi-stage pore catalyst, characterized in that: The preparation method comprises the following steps: (1) mixing a template, a solvent, a pore-enlarging agent, an acidic solution, and an aluminum source to obtain a mixture; (2) drying, keeping the mixture at a constant temperature and humidity, and heating the mixture in sequence to obtain a catalyst powder; (3) sequentially cooling and granulating the catalyst powder to obtain a multi-level porous catalyst; The template agent is a polyethylene glycol-polypropylene glycol copolymer.

2. The preparation method according to claim 1, characterized in that: The solvent includes ethanol; Preferably, the mass ratio of the template to the aluminum source is 1:(15-25); Preferably, the pore-enlarging agent comprises any one or a combination of at least two of trimethylbenzene, methacrylate or glucose; Preferably, the trimethylbenzene is 1,2,3-trimethylbenzene; Preferably, the mass ratio of the pore expanding agent to the aluminum source is 1:(10-15).

3. The preparation method according to claim 1 or 2, characterized in that: The acidic solution comprises an organic acid and / or an inorganic acid, preferably a combination of an organic acid and an inorganic acid; Preferably, the mass ratio of the acid in the acidic solution to the pore-enlarging agent is 1:(8-10); Preferably, the organic acid comprises any one of formic acid, acetic acid, malic acid, citric acid or salicylic acid, or a combination of at least two thereof; Preferably, the inorganic acid comprises any one or a combination of at least two of sulfuric acid, hydrochloric acid, carbonic acid or nitric acid; Preferably, the aluminum source comprises aluminum isopropoxide or aluminum n-butoxide; Preferably, the particle size of the aluminum source is 0.5-1 mm; Preferably, the molecular weight of the polyethylene glycol-polypropylene glycol copolymer is 12000-15000.

4. The preparation method according to any one of claims 1 to 3, characterized in that The mixing in step (1) comprises: adding the template into the solvent and stirring to obtain a mixed solution; premixing the mixed solution with the pore-enlarging agent to obtain a premix; and sequentially adding an acidic solution and an aluminum source into the premix; Preferably, the stirring speed is 300-400 r / min, and the stirring time is 0.5-1.5 h; Preferably, the premixing speed is 100-150 r / min, and the premixing time is 14-19 h; Preferably, the drying temperature is 45-55°C; Preferably, the drying time is 40-60 hours; Preferably, the stacking thickness of the mixture during the drying process is 4-10 cm.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the constant temperature and humidity static treatment is 35-45°C; Preferably, the relative humidity of the constant temperature and humidity static treatment is 5-8%; Preferably, the constant temperature and humidity static treatment time is 144-192h; Preferably, the stacking thickness of the mixture during the constant temperature and humidity static treatment is 5-10 cm.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The heating treatment includes sequentially heating and keeping warm; Preferably, the heating rate is 50-70°C / h; Preferably, the target temperature of the heating is 680-720°C; Preferably, the insulation time is 5-8h; Preferably, the atmosphere of the heating treatment includes any one of nitrogen, helium or argon, or a combination of at least two of them; Preferably, the cooling target temperature is 20-25°C.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) dissolving a polyethylene glycol-polypropylene glycol copolymer in a solvent, and stirring the mixture at a speed of 300-400 r / min for 0.5-1.5 h to obtain a mixed solution; (2) premixing the mixed solution with a pore expanding agent at a rotation speed of 100-150 r / min to obtain a premix, adding an acidic solution to the premix and stirring for 15-45 min, adjusting the pH to 4.6-5.4, and then adding an aluminum source to the premix to obtain a mixture; (3) drying the mixture at 45-55° C. for 40-60 h; then allowing the mixture to stand at a temperature of 35-45° C. and a relative humidity of 5-8% for 144-192 h; then heating the mixture to 680-720° C. at a rate of 50-70° C. / h and keeping the temperature for 5-8 h to obtain a catalyst powder; (4) Cooling the catalyst powder to 20-25° C. and granulating the powder to obtain a multi-level channel catalyst.

8. A multi-stage porous catalyst obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The multi-level pore channel catalyst has both macropore channels and mesopore channels.

9. The multi-stage porous catalyst according to claim 8, characterized in that: The pore size of the macropore channel is 100-200 nm; Preferably, the pore size of the mesoporous channel is 2-50 nm; Preferably, the particle size of the multi-stage pore catalyst is 3-5 mm; Preferably, the specific surface area of ​​the multi-stage pore catalyst is 300-450m 2 / g; Preferably, the porosity of the multi-level channel catalyst is 60-70%; Preferably, the shape of the multi-level porous catalyst includes any one of spherical, strip or cylindrical shapes, or a combination of at least two of them.

10. Use of a multi-stage porous catalyst obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The multi-stage pore catalyst is used for hydrolysis of carbonyl sulfide.

Citation Information

Patent Citations

  • Composite molecular sieve and hydrodesulfurization catalyst prepared with composite molecular sieve as carrier

    CN105251527A

  • Preparation method of catalyst capable of improving inactivation resistance in carbonyl sulfide hydrolysis reaction

    CN113332969A

  • Mesoporous metal oxides and processes for preparation thereof

    WO2014052482A1